Optimasi Metode Particle Swarm Optimization (PSO) Pada Prediksi Penilaian Apartemen - Lala Nilawati; Yuni Eka Achyani (Paradigma, 2019)
One property that is currently being glimpsed by investors is an apartment. Property consulting companies as one of the service provider companies that become a link between apartment owners and apartment enthusiasts, have an important task in terms of providing information about the assessment of the offered institutions. This study will conduct a trial on the accuracy of apartment assessment predictions using the Support Vector Machine (SVM) method, then will be compared again with the results of the accuracy of the assessment method Support Vector Machine (SVM) combined using the optimization method Particle Swarm Optimization (PSO). The results of the combination of the application of SVM and PSO are used to optimize attribute selection in apartment valuation to improve the accuracy of using the SVM method. This study shows that the Particle Swarm Optimization (PSO) Support Vector Machine (SVM) method is a pretty good method of data classification, because it can seen from the increase in accuracy of 2.84% and AUC of 0.003. Subjects (attributes) that affect apartment valuation are seen from rent prices (price range), city (apartment location), size (area), furnisihing (equipment), bedroom (number of bedrooms), bathroom (number of bathrooms) and maids badroom (number of maid rooms). The results of the attribute testing showed that city attributes (apartment locations), furnisihing (equipment) and maid badroom (number of maid rooms) greatly influenced the valuation of an apartment.